TRANSFORMASI DIGITAL DAN SISTEM INFORMASI: STRATEGI, TANTANGAN, DAN IMPLEMENTASI DALAM KONTEKS BISNIS MODERN - Serina Admi Yuliana; Nabila Putri Candra; Salsa Nabila; Intra Sepriansa; Alif Azhar; Ines Heidiani Ikasa (Journal of Research and Publication Innovation, 2025)
Digital transformation has become a strategic necessity for companies seeking to survive and remain competitive in the modern business era. This study aims to analyze the role of information systems in supporting digital transformation, review the readiness of information technology architecture, identify key challenges such as the digital divide and ethical issues, and evaluate e-commerce strategies as part of digital implementation. The research employs a qualitative method through a literature study. The findings indicate that information systems serve as the foundation for business process integration and data-driven decision-making. An adaptive and agile IT architecture is a crucial prerequisite for addressing rapid technological changes. The main challenges include limited access to technology, low levels of digital literacy, cybersecurity risks, and data privacy concerns. Meanwhile, e-commerce has proven effective in expanding market reach and improving business efficiency when supported by appropriate digital marketing strategies and optimal customer data management. The study concludes that the success of digital transformation is determined by organizational readiness, leadership support, workforce competency development, and strong technology governance.